Trans‐inclusive genetic counseling services: Recommendations from members of the transgender and non‐binary community. Issue 3 (11th November 2019) - Barnes, Heather; Morris, Emily; Austin, Jehannine
Abstract: The term transgender is used to describe individuals whose gender identity does not align with their sex assigned at birth. The term transgender can include individuals who identify as men, as women, as both of the traditional concepts of masculine and feminine gender, or neither masculine or feminine. The latter two gender identities may also be known as non‐binary or gender non‐conforming identities. Transgender individuals may attend genetic counseling for a variety of reasons, but current pedigree nomenclature does not adequately represent both sex assigned at birth (which is important for determining risk for certain conditions) and gender (which is important for providing trans‐inclusive care). We conducted an interpretive description (qualitative, interview based) study with individuals from the transgender community to gather insight on pedigree nomenclature and more broadly, how to provide safe and effective genetic counseling for transgender individuals. We conducted semi‐structured telephone interviews with individuals who identified as transgender or gender non‐binary, transcribed them verbatim, and checked them for accuracy before coding and inductively identifying themes. Among our eight participants, five identified as trans‐masculine, two as trans‐feminine, five as non‐binary/gender non‐conforming (some participants had more than one gender identity). From the interviews, we identified a single key, over‐arching theme: participants' felt it is the genetic counselor's responsibility to create safety and provide clarity about the clinical importance of both sex assigned at birth and gender identity for trans patients. Two specific strategies that counselors could use to achieve this safety and clarity were discussed extensively: (a) validating gender identity and (b) using inclusive and well‐defined pedigree symbols that denote both sex assigned at birth and gender identity. Our data have important practice implications in terms of the importance of validating gender identity and using respectful pedigree symbols.